The Willingness of Bystander to Perform CPR to the Patient with Out of Hospital Cardiac Arrest During the Pandemic Covid 19: A Literature Review - Zulmah Astuti; Misbah Nur Jannah (Proceedings of the International Conference on Nursing and Health Sciences, 2021)
Cardiac arrest is one of the emergency cases that requires immediate treatment. The Out of the Hospital Cardiac Arrest (OHCA) can happen anytime and everywhere with or without any sign. During a pandemic, OHCA often occurs at home and the patient have been found by family members as witness. unfortunately, based on the data The survival rate for patients with OHCA during the pandemic has decreased. There are several factors that cause this to happen, one of which is a decrease in bystander in performing CPR on patients. Bystander's willingness to perform CPR plays an important role in the chain of survival of patients with OHCA which affects patient outcomes. Based on this, a study was conducted on the willingness of bystander to perform CPR to the patient with out of hospital cardiac arrest (OHCA) during the pandemic covid 19. This research method is a literature review sourced from research journals conducted in 2019 to 2021 about the willingness of bystanders to perform CPR during the pandemic. The results seven journals that have been analysed show that most of the bystanders are willing to perform CPR with various conditions including Perform hands only CPR and if Personal Protective Equipment (PPE) is Avalaible. There are several conditions that cause the CPR bystander not to be willing to perform CPR, such as the fear of being infected, the absence of PPE and the victim is a stranger or unfamiliar person for bystander. Conclusion the willingness of bystanders to perform CPR on OHCA victims during the pandemic is still high, bystander perform hands only CPR and using PPE during the intervention.